The Effect of Conventional and Mini-Invasive Cardiopulmonary Bypass on Neutrophil Activation in Patients Undergoing Coronary Artery Bypass Grafting - Martina Kolackova; Jan Krejsek; Vladimir Svitek; Pavel Kunes; Jiri Mandak; Zdenka Holubcova; Vladimir Lonsky (Mediators of Inflammation)
Interleukin-10 (IL-10) is considered to be a cytokine with potent anti-inflammatory properties, which have been previously linked to increased incidence of sepsis. The level of IL-10 is elevated by cardiac surgery when cardiopulmonary bypass (CPB) and methylprednisolone are used. In our study, we compare the level of IL-10, IL-10 Receptor (IL-10R), and percentage of neutrophils between two groups of cardiac surgical patients undergoing Coronary Artery Bypass Grafting, both of which were not given methylprednisolone. The first group was operated with conventional CPB, while the second group was operated with minimally invasive CPB (mini-CPB). We detected enhanced level of IL-10 during surgery and at the end of surgery in both groups of patients. While no correlation between IL-10 and IL10R was found, IL-10 was positively correlated with increased percentage of neutrophils at the time points when the level of IL-10 peaked.